Nests and eggs of Greylag Geese in Galloway - Young, J G (Wildfowl, 1965)
Sixty eggs in 10 nests of Greylag Geese in Galloway in 1964 were measured. Their dimensions (average length 84.5 mm., breadth 59.2 mm.) were similar to those published for other British eggs which tend to be smaller than eggs from continental Europe. All 10 nests were successful, though 5 eggs failed to hatch. In a second group of nests, 6 out of 8 clutches were successful. At least 42 goslings were reared in the first group and 28 in the second. The sites and dimensions of the nests are described.